"We know about schistosomiasis but we know nothing about FGS": A qualitative assessment of knowledge gaps about female genital schistosomiasis among communities living in Schistosoma haematobium endemic districts of Zanzibar and Northwestern Tanzania. - Humphrey D Mazigo (Public Library of Science (PLoS), 2021)
Background Schistosoma haematobium causes urogenital schistosomiasis and is widely distributed in Tanzania. In girls and women, the parasite can cause Female Genital Schistosomiasis (FGS), a gynecological manifestation of schistosomiasis that is highly neglected and overlooked by public health professionals and policy makers. This study explored community members' knowledge, attitudes and perceptions (KAP) on and health seeking behavior for FGS. Methods/principal findings Using qualitative research methods-including 40 Focus Group Discussions (FGDs) and 37 Key Informant Interviews (KIIs)-we collected data from 414 participants (Males n = 204 [49.3%] and Females n = 210 [50.7%]). The study engaged 153 participants from Zanzibar and 261 participants from northwestern Tanzania and was conducted in twelve (12) purposively selected districts (7 districts in Zanzibar and 5 districts in northwestern Tanzania). Most participants were aware of urogenital schistosomiasis. Children were reported as the most affected group and blood in urine was noted as a common symptom especially in boys. Adults were also noted as a risk group due to their involvement in activities like paddy farming that expose them to infection. Most participants lacked knowledge of FGS and acknowledged having no knowledge that urogenital schistosomiasis can affect the female reproductive system. A number of misconceptions on the symptoms of FGS and how it is transmitted were noted. Adolescent girls and women presenting with FGS related symptoms were reported to be stigmatized, perceived as having a sexually transmitted infection (STI), and sometimes labeled as "prostitutes". Health seeking behavior for FGS included a combination of traditional medicine, self-treatment and modern medicine. Conclusion/significance Community members living in two very different areas of Tanzania exhibited major, similar gaps in knowledge about FGS. Our data illustrate a critical need for the national control program to integrate public health education about FGS during the implementation of school- and community-based mass drug administration (MDA) programs and the improvement of water, sanitation and hygiene (WASH) facilities.